Seventh Annual California Apartment Conference - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the Seventh Annual California Apartment Conference. The group is shown in front of the San Jose Civic Auditorium and the Hotel Sainte Claire on East San Carlos Street in the background.